LOST IN TRANSLATING THE DIVINE MESSAGE: Different Perspectives of Indonesian Muslim Feminists on Polygamy Verses in the Qur’an - Muthmainnah, Yulianti; Mundzir, Ilham; Razak, Yusron; Arif, Nasr Muhammad (JOURNAL OF INDONESIAN ISLAM, 2025)
The Indonesian government, through the Ministry of Religion, has officially translated the Qur'an to understand the content and context of the Qur'an. This translation became the only official translation for many years and serves as a public reference. However, such translation is not always well-received; some agree with it by offering notes, while some disagree and suggest new translations because they are considered biased, including gender bias. One of the verses that reflects gender bias is the translation of the Qur'an al-Nisa [4]:3 regarding polygamy. This paper analyzes the translation of the Qur'an by comparing the opinions of two Indonesian scholars, namely Siti Musdah Mulia and Faqihuddin Abdul Kodir. This research employs a qualitative methodology, focusing on literature study, interviews, and lecture observations conducted by the two scholars. This paper concludes that Kodir disagreed with the government's translation and offered a new translation regarding the verse on polygamy, while Mulia gave a different interpretation and approach to understanding the text.